PENGEMBANGAN SISTEM INFORMASI TUGAS AKHIR MAHASISWA BERBASIS ANDROID MOBILE APPLICATION DI JURUSAN PENDIDIKAN AGAMA ISLAM IAIN PONOROGO - Nurbawani, Aris; Hasnawan, Dedi (IAIN PONOROGO, 2024)
The Department of Islamic Religious Education (PAI) of the Faculty of Tarbiyah and Teacher Training at IAIN Ponorogo has for years carried out a manual thesis control process for students who register and have fulfilled academic and administrative requirements. There are many problems and difficulties faced by the PAI Department starting from the mechanism for submitting titles by students, checking and accepting titles one by one by the Department, announcement of ACC titles, filling out research matrices, to controlling the making of research proposals which later students will be tested and get supervisors. On the other hand, the demands of the times in the all-digital era require that every higher education institution compete to provide services to students by utilizing the latest technology. Technology-based services are a necessity as a factor in the competitiveness of higher education institutions. The e-learning system in the Islamic Religious Education department at IAIN Ponorogo does not yet provide facilities for the process of submitting final project titles, but only for uploading final project files and assessing seminar proposal and thesis exams. Almost all students majoring in PAI IAIN Ponorogo have smartphones, so this potential is very interesting if a student final assignment information system based on android mobile application is developed. The purpose of this research is to develop an Android-based Final Assignment information system at the Department of PAI IAIN Ponorogo that is valid, practical, and effective and to analyze its quality. This study uses the method of Research and Development (Research and Development). This research was conducted using the Winston W. Royce waterfall procedure. The results of this study are that the development of an android-based final project information system at the Department of PAI IAIN Ponorogo is carried out in several main stages: needs analysis, design (modeling and interface), implementation, and quality testing. The quality of this Android-based final project information system is tested on the aspects of functional suitability, compatibility, and usability. Testing the functional suitability and compatibility aspects is carried out by observing various different smartphone devices. Testing the functional suitability aspect of 100% and compatibility also obtained a score of 100%. Testing the usability aspect is carried out by conducting a survey using a questionnaire adopted from the USE Questionnaire questionnaire by Arnold M. Lund with necessary adjustments. The results of testing the usability aspect obtained an assessment score of 85.4% with details on the aspects of usefulness (86.67), ease of use (83.75), ease of learning (85), and satisfaction (86.43).